PEMBERDAYAAN KOPERASI GUNA MENINGKATKAN KESEJAHTERAAN ANGGOTA DALAM MENDUKUNG KETAHANAN EKONOMI KELUARGA (Studi Kasus di Koperasi Primer Lemhannas RI) - , Hary Dwiantoko, Prof. Dr. Sudaryono, SU ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Cooperatives as one of the business entity that is engaged in Indonesia's economy is currently experiencing a dismal times caused due to lack of competitiveness that is owned by a cooperative against other business entities as well as a lack of interest in the community to join the cooperative especially urban communities. While this is just growing quantity of cooperation without any quality improvement. This research is intended to acknowledge the efforts made and the obstacles facing Cooperatives in improving the welfare of the National Defence Institute of RI as well as members of the strategy pursued in overcoming these barriers. This research was conducted at the National Defence Institute of RI Cooperative by taking samples as much as 88 respondents as well as using the method of data collection through the spread sheet questionnaire, that highlight the collection and analysis of written texts and it was revealed in the questionnaire. For complements and reinforces the information and data, conducted interviews with the parties associated with the Cooperative National Defence Institute of RI. After the study, can be identified that National Defence Institute of RI Cooperative has done some effort in improving the welfare of its members, i.e. the granting of loans to members, the granting of funds administering SHU, stipend for members or family members who died, granting lebaran presents and awarding scholarships for children of members who are top achievers. However, until this research done, National Defence Institute of RI Cooperative is still not optimal in improving the welfare of members and in order to support the economic resilience of the family. It is known from the existence of barriers faced by National Defence Institute Cooperative, such as lack of capital, strategic location of stores that are less, bad credit and still low participation member. The study concluded that to improve the welfare of the members and support family economic security need to be done a couple of cooperative empowerment strategies, i.e. increase capital cooperative, improve services, and to improve the participation of members. Through some of these strategies, the welfare of members will increase, with a good level of prosperity will shape the economic resilience of the family firm. Materialize economic resilience is a strong and resilient family can face each threat, challenges, obstacles and distractions that come both from within and from outside.